Powder metallurgy synthesis of Pd-doped MoS2: A structural and morphological study - Nogueira, Jonas Miguel; Oliveira, Adhimar Flavio; Rubinger, Rero Marques; Correa Carvalho, Celso Henrique (Journal of Applied Materials and Technology, 2025)
This study reports the synthesis and structural characterization of palladium (Pd)-doped molybdenum disulfide (MoS?) produced via the powder metallurgy route. The primary objective was to investigate how Pd incorporation influences the structural, morphological, and electrical properties of MoS?, thereby demonstrating the advantages of powder metallurgy compared to conventional synthesis techniques. The materials were analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM) coupled with energy-dispersive spectroscopy (EDS), Fourier-transform infrared spectroscopy (FTIR), and Raman spectroscopy. XRD confirmed the retention of the hexagonal MoS? phase without the formation of secondary Pd-related phases, indicating successful substitutional doping. SEM–EDS analyses revealed a uniform Pd distribution and progressive morphological evolution with increasing Pd content, characterized by enhanced surface roughness and improved particle dispersion. FTIR and Raman spectra showed modifications in bonding environments and vibrational modes, evidencing the structural influence of Pd atoms on the MoS? lattice. Electrical measurements, performed using both I–V and four-point probe methods, demonstrated a conductivity increase from 9.6 × 10?? S·m?¹ for pure MoS? to 1.6 × 10?? S·m?¹ and 1.9 × 10?? S·m?¹ for the 1% and 2% Pd-doped samples, respectively. This enhancement is attributed to the higher charge carrier density and improved interlayer charge transport induced by Pd doping. These findings confirm that powder metallurgy provides an effective and scalable synthesis pathway for achieving homogeneous Pd incorporation in MoS?. The resulting materials exhibit excellent structural integrity and enhanced electrical performance, making them promising candidates for catalytic, sensing, and energy storage applications.